Activation of human T cells by FcR nonbinding anti-CD3 mAb, hOKT3γ1(Ala-Ala) - Kevan C. Herold; Joshua B. Burton; Fleur Francois; Ena Poumian-Ruiz; Mariela Glandt; Jeffrey A. Bluestone (The Journal of Clinical Investigation, 2003)
Dimeric Fc receptor (FcR) nonbinding anti-CD3 antibodies have been developed to minimize toxicities associated with classical anti-CD3 monoclonal antibodies (e.g., OKT3). Studies with murine analogs of non-FcR–binding antibodies have shown reduced mitogenicity compared to OKT3. In a trial of an FcR nonbinding humanized anti-CD3 mAb hOKT3γ1(Ala-Ala) for treatment of patients with type 1 diabetes, we found significant increases in IL-10 and IL-5 in the serum of 63% and 72% of patients, respectively, and TNF-α and IL-6 levels that were lower than those previously reported following OKT3 therapy. The activation signal delivered by hOKT3γ1(Ala-Ala) was associated with calcium signaling and cytokine production by previously activated human cells in vitro. However, the production of IL-10, compared to IFN-γ on a molar basis, was greater after culture with hOKT3γ1(Ala-Ala) than with OKT3. Flow cytometric studies confirmed that OKT3 induced IFN-γ and IL-10 production, but hOKT3γ1(Ala-Ala) induced only detectable IL-10 production in CD45RO+ cells. Moreover, in vivo, we found IL-10+CD4+ T cells after drug treatment. These cells were heterogeneous but generally CD45RO+, CTLA-4–, and expressed CCR4. A subgroup of these cells expressed TGF-β. Thus, the non-FcR binding anti-CD3 mAb, hOKT3γ1(Ala-Ala) delivers an activation signal to T cells that is quantitatively and qualitatively different from OKT3. It leads to the generation of T cells that might inhibit the autoimmune response and may be involved in the beneficial effect on β cell destruction in Type 1 diabetes.